Tax Knowledge and Policy Implementation as Determinants of Hotel Taxpayer Compliance: Evidence from the Serpong Tax Office - Indra Tribuana Putra (CV. Era Digital Nusantara, 2026)
This study examines the role of tax knowledge and policy implementation in shaping hotel taxpayer compliance at the Serpong Tax Office. While national tax compliance rates show improvement, local-level enforcement and compliance in specific service sectors, such as hospitality, remain under-researched, leaving a critical gap in regional revenue optimization. Using a quantitative explanatory design, the research included 81 hotels and lodgings as the population, with saturated sampling. Primary data were collected through questionnaires and interviews, supported by secondary sources. Data analysis employed classical assumption tests and multiple regression using SPSS 20. The findings reveal that tax knowledge has a positive and significant effect on taxpayer compliance (t = 3.749, p < 0.05). Policy implementation also shows a positive and significant effect (t = 3.479, p < 0.05). Simultaneously, both variables strongly influence compliance (F = 176.939, p < 0.05), with an R2 of 0.819, indicating that 81.9% of compliance variation is explained by these factors. This study highlights the critical role of taxpayer knowledge and consistent policy implementation in enhancing compliance. Practically, it implies that regional tax authorities must move beyond generic dissemination by implementing targeted digital workshops, integrating e-filing tailored for hospitality businesses, and enforcing transparent bureaucratic procedures to directly minimize local administrative friction.